Plasma level of alpha-synuclein oligomers as a biomarker for isolated rapid eye movement sleep behavior disorder diagnosis and progression: a prospective cohort study - Ying, Chao; Zhang, Hui; Wang, Ting; Li, Yuan; Mao, Wei; Hu, Songnian; Zhao, Lifang; Cai, Yanning (Frontiers in Neurology, 2024)
Background: Alpha-synuclein oligomers (o-α-syn) are pivotal in the pathogenesis of α-synucleinopathy. Isolated rapid eye movement (REM) sleep behavior disorder (iRBD) serves as an early indicator of the disease, offering insights into disease mechanisms and early intervention.Nevertheless, the diagnostic and predictive potential of o-α-syn in iRBD remains largely unexplored.This study aimed to evaluate the plasma levels of o-α-syn in patients and investigate their utility as biomarkers for diagnosis of and predicting phenoconversion in iRBD.Methods: A total of 143 participants, including 77 polysomnography-confirmed iRBD patients and 66 normal controls (NC), were recruited for this longitudinal observational study. Baseline clinical assessments and plasma collection were conducted for all iRBD patients, with 72 of them undergoing regularly prospective follow-up assessments for parkinsonism or dementia. Plasma levels of o-α-syn were quantified using enzyme-linked immunosorbent assay, and were compared between groups using a general linear model adjusted for age and sex. The diagnostic performance of plasma o-α-syn in iRBD was evaluated by area under the receiver operating characteristic curve (AUC) with 95% CI. Cox regression analysis and Kaplan-Meier survival curves were employed to assess the predictive value of plasma o-α-syn for phenoconversion in iRBD.Results: Plasma o-α-syn levels did not exhibit statistically significant differences among iRBD converter patients, iRBD nonconverter patients, and NC. The AUC for distinguishing NC from iRBD was 0.52 (95% CI: 0.42-0.62, P = 0.682). Spearman correlation analysis revealed a significant positive correlation between plasma o-α-syn levels and MOCA scores in the iRBD group (P < 0.001). Subgroup analyses indicated that iRBD patients with cognitive decline (P =0.058) and depressive symptoms (P = 0.017) had notably lower o-α-syn levels compared to those without such symptoms. Over a median follow-up period of 5.83 years, 26 iRBD patients developed neurodegenerative synucleinopathies. Cox regression and Kaplan-Meier survival curve analyses indicated that plasma level of o-α-syn lacked a predictive value for disease conversion in iRBD patients.Despite a potential role in the pathophysiology of iRBD, o-α-syn are not appropriate biomarkers for diagnosing or predicting disease progression. While this study offers insights into the pathogenesis of iRBD and neurodegenerative synucleinopathies, further large-scale longitudinal studies are warranted to validate these findings.